Moving neuromuscular disorders research forward: from novel models to clinical studies - Maaike van Putten; Julija Hmeljak; Annemieke Aartsma-Rus; James J. Dowling (The Company of Biologists, 2020)
Neuromuscular disorders (NMDs) encompass a diverse group of genetic diseases characterized by loss of muscle functionality. Despite extensive efforts to develop therapies, no curative treatment exists for any of the NMDs. For multiple disorders, however, therapeutic strategies are currently being tested in clinical settings, and the first successful treatments have now entered clinical practice (e.g. spinraza for spinal muscular atrophy). Successful clinical translation depends on the quality and translatability of preclinical findings and on the predictive value of the experimental models used in their initial development. This Special Issue of Disease Models & Mechanisms has a particular focus on translational research for NMDs. The collection includes original research focusing on advances in the development of novel in vitro and in vivo models, broader understanding of disease pathology and progression, and approaches to modify the disease course in these models. We also present a series of special articles and reviews that highlight our understanding of cellular mechanisms, biomarkers to tract disease pathology, the diversity of mouse models for NMDs, the importance of high-quality preclinical studies and data validation, and the pitfalls of successfully moving a potential therapeutic strategy to the clinic. In this Editorial, we summarize the highlights of these articles and place their findings in the broader context of the NMD research field.